Agricultural law saving the world, or making too high demands? On the methodology for integrating non-agricultural claims into European agricultural law - Norer, Roland (Przegląd Prawa Rolnego, 2021)
In the course of its development, starting with the organisation of agricultural markets, the Common Agricultural Policy has been confronted with many different, also non-agricultural problems. It had to respond to the requirements of environmental protection, structural and social policy, animal welfare, energy policy or climate protection. Nowadays, there are three different methods by which the relationship between agricultural law and non-agricultural legal issues is legally shaped: separation, connection and integration.